Effect of acid distribution and pore structure of ZSM-5 on catalytic performance. Issue 10 (4th July 2022) - Jin, Runze; Ma, Ke; Xu, Shutao; Wei, Yingxu; Song, Lijuan; Li, Zhijun; Zhang, Penghui; Wang, Yufeng; Wang, Jiaofei; Zhang, Zhuangzhuang; Ma, Xiaoxun; Hu, Haobin; et al.
Abstract : Zeolite with crystal intracrystalline pore structure with less acid on the outer surface. Abstract : Zeolites are widely used in acid catalysis, shape-selective catalysis, and other fields because of their unique structural characteristics. Zeolites have long and narrow pore structures, which limits the diffusion of reactants and products. However, in traditional alkali desilication processes, the acid center of the zeolite is exposed to the outer surface, inhibiting microporous shape selection and resulting in a reduction of target product selectivity. Consequently, a "seesaw" relationship exists between conversion and selectivity in zeolite catalysis, and this is one of the main bottlenecks in the development of this field. Developing an alkali treatment strategy that breaks this "seesaw" relationship and is suitable for shape-selective catalysis is a significant challenge. Therefore, we systematically studied the effects of different alkali treatment strategies on the physicochemical properties of an HZSM-5 zeolite, including properties such as acid distribution, acid strength, acid amount, Si/Al coordination state, and diffusion performance. We then further studied the effects of these physicochemical properties on catalytic performance (conversion and selectivity). The results show that a zeolite prepared by the dissolution–recrystallization method forms a rich intracrystalline structure with good accessibility in the crystal, and the silicon-rich outer surface inhibits a surface side reaction. This zeolite was applied to the alkylation of biphenyl with emphasis on selectivity and conversion, and it was found that both were significantly improved by the alkali treatment strategy. In a methanol to propylene (MTP) reaction, this zeolite catalyst also showed good catalytic life and selectivity.